Profile of CPAP-prescribing physicians in Ontario, Canada: A secular trend analysis. Issue 1 (2nd January 2019) - Grant-Orser, Amanda; Bray-Jenkyn, Krista; Allen, Britney; George, Charles F.; Shariff, Salimah Z.; Povitz, Marcus
Abstract: BACKGROUND: The prevalence of sleep disorders, such as obstructive sleep apnea, is on the rise worldwide. In Canada, sleep medicine has not been recognized as a unique discipline, and a minimal amount is known about those who practice sleep medicine. The objectives of this study were to quantify the number of physicians practicing sleep medicine and to describe their demographic and clinical practice. METHODS: We conducted a population based study using linked health administrative data in Ontario, Canada between 2006 and 2013. Sleep physicians were determined to be active if they initiated more than one patient on continuous positive airway pressure in a given year. For each year, we determined the profiles of physicians practicing sleep medicine, including demographics, their primary specialty, and clinical practice characteristics. RESULTS: The number of active sleep physicians in Ontario increased from 133 to 190 or 1.3 to 1.8/100 000 Ontario residents over the study period. Respirology (53%–58%) was the predominant specialty, followed by psychiatry (13%–16%). Sleep physicians were mostly male (75%–84%), with a mean age ranging from 50 to 51 years. Over the years, an increasing proportion completed their undergraduate medical school training outside of Canada (27%–31%). Of their total volume of consultations, 31%–36% were sleep related. CONCLUSIONS: Although the number of physicians practicing sleep medicine is steadily increasing, most devote less than a third of their time to sleep disorders. These findings should be considered when designing provincial and national strategies to increase the capacity of sleep medicine in order to meet the increasing demand.